THE IMPORTANCE OF EMOTIONAL AND MORAL RESILIENCE IN TODAY’S DEMANDS - Tajiboyeva Odinakhon Rustamjon kizi,Ismoilova Rayhona Ulug'bek kizi (International Journal of Literature and Language Studies, 2026)
This article analyzes the role of emotional and moral resilience in human life and professional activity in the context of globalization and rapid information exchange. It also scientifically explains the relationship between emotional stability, moral values, and psychological adaptability of an individual. The study reveals the significance of emotional and moral resilience in education, medicine, and social relations.